2017
DOI: 10.1590/1980-5918.030.001.ao17
|View full text |Cite
|
Sign up to set email alerts
|

Functional capacity assessment of upper limbs in healthy young adult subjects

Abstract: Introduction: Assessing the functional capacity of the upper limbs (UL) is essential to direct treatments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(24 reference statements)
3
3
1
Order By: Relevance
“…The 6PBRT results showed a week correlation with the level of physical activity as assessed by the HAP, which corroborates the findings of Ohara et al 24 This can be explained by the fact that the 6PBRT does not lead to a significant cardiorespiratory demand. Among patients with COPD, 6PBRT results correlate with arm ALD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The 6PBRT results showed a week correlation with the level of physical activity as assessed by the HAP, which corroborates the findings of Ohara et al 24 This can be explained by the fact that the 6PBRT does not lead to a significant cardiorespiratory demand. Among patients with COPD, 6PBRT results correlate with arm ALD.…”
Section: Discussionsupporting
confidence: 90%
“…Among patients with COPD, 6PBRT results correlate with arm ALD. 11 Physical exercise is known to improve muscle flexibility, as well as to increase endurance and motor coordination, 24 - 27 but this was not observed here, because we conducted a cross-sectional study and there was no physical training followed by determination of whether there was improvement in performance on the 6PBRT.…”
Section: Discussionmentioning
confidence: 81%
“…This can be explained by the fact that exercising muscles lead to an increase in the metabolic demand, which is met through various changes in the respiratory and circulatory system. The sympathetic nervous system plays a major part in increasing heart rate, respiratory rate and blood pressure-systolic as well as diastolic during exercise [27].Our findings are similar to a study done by Ohara et al, in which the pre-post vitals after performing 6PBRT was checked, and found to have significant correlation [28].…”
Section: Discussionsupporting
confidence: 90%
“…We hypothesized that variables such as weight, height, BMI, arm length, arm and forearm circumference, shoulder, elbow flex- ors-extensors strength and grip strength would be the predictors of the number of rings completed in the test in 6 minutes. There was no significant correlation seen among height, weight and BMI in either gender with the number of rings which corroborates with the findings of Ohara et al [28]. BMI does not interfere with the performance of the test, probably due to the fact that 6PBRT does not intend to test the exercise capacity or intolerance through full-body activities, rather the participants are seated on a chair throughout the test.…”
Section: Discussionsupporting
confidence: 89%
“…(31,32) However, a study that assessed arm function using the six-minute pegboard and ring test, the purpose of which is to move as many rings as possible in 6 min, found no correlation between test performance and BMI. (33) These findings differ from those in the present study; however, we should take into consideration that the sample of that study was younger (mean age of 23.41 ± 3.58 years among the men and 23.27 ± 3.0 years among the women) and had a lower BMI (25.09 ± 3.91 kg/m 2 among the men and 22.26 ± 2.36 kg/ m 2 among the women), which may have affected the results. In the present study, the mean age overall was 55.87 ± 14.67 years, and the mean BMI was 26.59 ± 3.75 kg/m 2 , classified as overweight.…”
Section: Discussionmentioning
confidence: 99%